A survey of pediatric urology fellowship applicants: past priorities to guide future possibilities. Issue 6 (December 2022) - Ernst, Michael; Ebert, Kristin; Rehfuss, Alexandra; McLeod, Daryl; Alpert, Seth
Summary: Background: The number of applicants to pediatric urology fellowships is often lower than the available positions (chart), giving applicants significant influence over where they ultimately match. Historically, interviews were conducted at individual hospitals, in-person, with residents bearing most costs. The objective of this study was to understand the factors associated with where applicants decide to apply, interview, and match for fellowship, as well as barriers within this process. Methods: A 24-question survey was sent via email to all applicants who successfully matched into pediatric urology fellowship from 2013 to 2019. Questions included: demographics; factors associated with where they applied, interviewed, and ranked; and barriers within the application process. Results: A total of 126 recent and current fellows were contacted, and 73 (60%) completed the full survey (51% male and 49% female). On average, respondents applied to 10 programs, interviewed at 9, and ranked 8. The most important factors in choosing where to apply/interview were: volume of surgical cases, diversity of surgical cases, and advice from mentors. The most important factors when making a rank list were: clinical autonomy, reputation of program, and structure of program. Hospital facilities were only rated "important" by 12% of respondents. 82% (60 respondents) faced at least one personal or professional barrier during the application process. The most common barrier was "cost of interviewing" (59%, 43 respondents). Personal vacation time was used by 61% of applicants during interviews, with 37% using more than 5 days. Discussion: This study is the first to explore the factors that applicants consider when choosing where to apply, interview, and rank for pediatric urology fellowship. This information is important to understand due to the current supply and demand of fellowship positions. We are limited by extrapolating more general conclusions about applicants as a whole from a survey with a 60% response rate and the lack of an available validated survey in this realm. Conclusions: This study has shown that most pediatric urology fellowship applicants apply to programs primarily based on perceived surgical volume and reputational factors. These same factors are used when making a rank list. Many applicants faced personal or professional barriers during the application process, largely due to costs and time away from work and family. While recent interviews have transitioned to a virtual format by necessity, prior applicants did not rate hospital facilities as important to them. Overall, there is room to improve this process based on such feedback.